2002
DOI: 10.1007/s11664-002-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlating discrete orientation and grain size to the sputter deposition properties of tantalum

Abstract: Recent findings indicate that the erosion behavior of tantalum sputtering targets varies across regions of different discrete crystal orientation. Specifically, bands of sharp, localized (100) texture amid the microstructure and aligned parallel to the sputtering surface of planar tantalum targets have been shown to resist erosion. Referencing theoretical models and characterization studies of wrought tantalum, this paper explores the relationship between discrete crystallographic texture and grain size of tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 16 publications
(14 reference statements)
0
19
0
1
Order By: Relevance
“…Recently, Ta sputtering target used in the integrated circuit (IC) industry to fabricate copper diffusion barrier has attracted more and more attention [1][2][3]. Early studies have confirmed that both grain size and crystallographic orientation can play an important role in the sputter deposition properties of Ta [4,5]. The deposition rate of thin film drops with increasing grain size, and the film thickness can be uniform only when the grain size is within a certain range [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ta sputtering target used in the integrated circuit (IC) industry to fabricate copper diffusion barrier has attracted more and more attention [1][2][3]. Early studies have confirmed that both grain size and crystallographic orientation can play an important role in the sputter deposition properties of Ta [4,5]. The deposition rate of thin film drops with increasing grain size, and the film thickness can be uniform only when the grain size is within a certain range [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tantalum (Ta), body-centered-cubic (BCC) structure, is a refractory metal with a series of excellent physical and chemical properties, such as corrosion resistance and good ductility, which makes it an ideal material for microelectronics and sputtering targets [1]. The quality of the sputtered film plays a key role in the semiconductor integrated circuit industry, and the grain size and crystal orientation distribution of the sputtering target have a direct influence on the quality of the sputtered film [2,3]. Different crystal orientations and grain size can lead to the difference in sputtering rates during magnetron sputtering [4].…”
Section: Introductionmentioning
confidence: 99%
“…The (100) texture bands found in Ta are comprised of striations of recovered or polygonized grains, whereas a matrix of primary (111) texture is characterized as having a fine, equiaxed, grain structure. 10,11 Fabrication of Ta plate by rolling typically results in inhomogeneous crystallographic textures and grain sizes with strong through-thickness gradients. 12 Depending upon the through-thickness position in the plate at which the microstructure is evaluated, one might find a predominantly (100) or (111) texture component (among other variants), resulting in significantly differing sputtering performance as a function of through-thickness position.…”
Section: Introductionmentioning
confidence: 99%